Dientes - Kingsley, Imogen (Minneapolis, MN : Bullfrog Books are published by Jump!, 2018)
"Carefully leveled text and vibrant photographs introduce early readers to the structure and function of the teeth. Includes picture glossary and index"--
Includes index.
Ages 5-8.
K to grade 3.
Keywords: Teeth -- Juvenile literature; Anatomy -- Juvenile literature